RESEPSI HADIS TENTANG ISTIBTHA DALAM KONTEN REELS INSTAGRAM (TINJAUAN ATAS AKUN @KHALIDBASALAMAHOFFICIAL) - Rinaldi, Risvan (Fakultas Ushuluddin, Adab, dan Dakwah UIN Sultan Aji Muhammad Idris Samarinda, 2025)
Abstract This study analyzes the reception of hadiths conveyed through the Instagram Reels platform. The background of this research is driven by the rapid development of digital media, which influences the way religious messages, especially hadiths, are delivered and received. Instagram Reels, as a feature of Instagram, allows the presentation of short-duration video content that is more engaging to the younger generation and easier to absorb compared to longer videos. This study raises two research questions: first, the form of hadith reception and responses to the hadith content on the Reels Instagram account @khalidbasalamahofficial; and second, the functional reception analysis of the hadith content on the Reels Instagram account @khalidbasalamahofficial. This study employs a qualitative method with a field and library research approach. Primary data is obtained by identifying hadith content on the Reels Instagram account @khalidbasalamahofficial, while secondary data consists of relevant literature, both online and offline, as well as journals discussing hadiths. Data collection techniques are carried out through documentation study, which includes screenshots and an analysis of the comments on the uploaded videos.The results of this study show that, first, the shift of hadith texts from print format to visual media (video) makes the practice of hadith reception more flexible, allowing the messages to be more easily received by Instagram users. Second, it was found that positive responses demonstrate a more dominant functional reception compared to negative responses. This is reflected in the screenshots and analysis of comments on the uploaded videos, which indicate that the hadiths presented are well-received by the audience.